High-molecular slow-release coating material for double-layer slow-release composite tableted candy and preparation process of high-molecular slow-release coating material

By combining ternary polymer substrates and using a double-layer core design, the contradiction between rapid release and long-lasting sustained release in the sustained-release coating technology of compressed candies is resolved, achieving stable release of active ingredients and integrity of the coating layer, making it suitable for the industrial production of functional compressed candies.

CN121286568APending Publication Date: 2026-01-09ACORN MEIJIAN IND INVESTMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511829105.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-05
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing sustained-release coating technologies for compressed candies cannot simultaneously meet the needs of both immediate release and long-lasting sustained release, and there are problems such as coating layer brittleness and peeling, which affect product stability and release effect.

Method used

A ternary polymer matrix compound system is adopted, combined with a double-layer core design, and the synergistic effect of hydrophilic and hydrophobic components is used, along with functional additives and precise process parameters, to prepare double-layer sustained-release composite compressed candy.

Benefits of technology

It achieves efficient stepwise sustained release of different active ingredients, improves product stability and coating integrity, and meets the stringent requirements of industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of food processing, in particular to a macromolecular sustained-release coating material for a double-layer sustained-release composite tablet candy and a tablet candy prepared from the macromolecular sustained-release coating material, the coating material comprises a macromolecular base material, a plasticizer, a pore-foaming agent, an anti-sticking agent, a functional auxiliary agent and a solvent; the polymer base material comprises hydroxypropyl methylcellulose, ethyl cellulose and polyacrylic resin; the tablet candy comprises a double-layer core body, the double-layer core body comprises an inner-layer quick-release core and an outer-layer slow-release core, the inner-layer quick-release core comprises a quick-release active component, a filler, an adhesive and a lubricant, and the outer-layer slow-release core comprises a slow-release active component, a slow-release base material, a filler and a lubricant. The type of the sustained-release base material is matched with that of the hydroxypropyl methylcellulose in the coating material. A ternary polymer base material compounding system is adopted, and efficient stepped slow release of different active ingredients is achieved through the synergistic effect of hydrophilic and hydrophobic components and in combination with the structural design of a double-layer core body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of food processing technology, specifically to a polymeric sustained-release coating material for double-layer sustained-release composite compressed candy and its preparation process. Background Technology

[0002] As an important carrier for functional foods and health products, the sustained-release coating technology of compressed candies directly affects the release efficiency and stability of active ingredients. Existing sustained-release coating technologies for compressed candies mainly fall into two branches, both of which suffer from core defects that are difficult to overcome.

[0003] One type of existing technology uses a single polymer substrate with a single-layer core design. These substrates are mostly of a single type, either hydrophilic or hydrophobic, and cannot simultaneously meet the dual requirements of immediate release and long-lasting sustained release. This leads to interference between the release rhythms of different active ingredients, making it difficult to achieve differentiated release effects. Another type of existing technology attempts to use binary substrates, but fails to adjust the solvent ratio according to the substrate's solubility or match the amount of plasticizer according to the substrate's characteristics. This makes the coating layer prone to problems such as brittleness and peeling, affecting product stability. At the same time, existing technologies generally neglect the synergistic design of the core and coating layer, mostly using a single-layer core structure, which cannot form a synergistic release effect with the coating material. In addition, the use of additives is haphazard. The type and amount of pore-forming agents and functional additives are not precisely controlled according to the release requirements, and process parameters are not dynamically adjusted according to the substrate characteristics and additive stability. This leads to problems such as uncontrolled release, degradation of active ingredients, and poor physical properties, failing to meet the comprehensive requirements of step-wise sustained release, intact coating, high stability, and excellent physical properties in industrial production. Summary of the Invention

[0004] The purpose of this invention is to address the shortcomings of existing technologies by proposing a polymeric sustained-release coating material for double-layer sustained-release composite compressed candy and its preparation process.

[0005] To achieve the above objectives, this invention proposes a polymeric sustained-release coating material for double-layer sustained-release composite compressed candy and compressed candy prepared therefrom. The coating material comprises a polymeric matrix, a plasticizer, a pore-forming agent, an anti-adhesive agent, a functional additive, and a solvent. The polymeric matrix comprises hydroxypropyl methylcellulose, ethyl cellulose, and polyacrylic acid resin. The compressed candy comprises a double-layer core, which includes an inner immediate-release core and an outer sustained-release core. The inner immediate-release core comprises an immediate-release active ingredient, a filler, a binder, and a lubricant. The outer sustained-release core comprises a sustained-release active ingredient, a sustained-release matrix, a filler, and a lubricant. The sustained-release matrix is ​​compatible with the type of hydroxypropyl methylcellulose in the coating material.

[0006] Preferably, the hydroxypropyl methylcellulose is selected from at least one of K4M, K15M, K100M, and K25M; and the polyacrylic acid resin is selected from at least one of Eudragit RS30D and Eudragit RL30D.

[0007] Preferably, the plasticizer is selected from at least one of triethyl citrate, diethyl phthalate, and glycerin.

[0008] Preferably, the pore-forming agent is selected from at least one of lactose, polyethylene glycol, and mannitol, and the polyethylene glycol is selected from at least one of type 4000, type 6000, and type 8000.

[0009] Preferably, the functional additive is selected from at least one of β-cyclodextrin, tea polyphenols, vitamin E, and rosemary extract; the anti-adhesive is selected from at least one of talc and micronized silica gel; and the solvent is selected from at least one of aqueous ethanol and aqueous isopropanol.

[0010] A preparation process for a double-layer sustained-release compound compressed candy includes the following steps: (1) Preparation of coating solution: The polymer substrate is dissolved in a solvent, then plasticizer, pore-forming agent and anti-adhesion agent are added for dispersion, and finally functional additives are added and degassed to obtain coating solution; the polymer substrate includes hydroxypropyl methylcellulose, ethyl cellulose and polyacrylic acid resin; (2) Preparation of double-layer core: Prepare inner layer fast-release core material and outer layer slow-release core material respectively, and press the two materials in sequence to form a double-layer core; (3) Coating and curing: The coating liquid is coated onto the surface of the double-layer core using a coating equipment, and then cured to obtain a double-layer slow-release composite compressed candy.

[0011] Preferably, in step (1), the temperature is controlled within a specific range when dissolving the polymer substrate, the dispersion process adopts high-speed shearing, and the degassing process adopts ultrasonication.

[0012] Preferably, in step (2), a double-layer tablet press is used to press the double-layer core, and the pressing process controls a specific pressure. The inner layer immediate-release core material contains immediate-release active ingredients, fillers, binders and lubricants, and the outer layer sustained-release core material contains sustained-release active ingredients, sustained-release substrate, fillers and lubricants. The sustained-release substrate is compatible with the hydroxypropyl methylcellulose type in the polymer substrate.

[0013] Preferably, in step (3), the coating equipment is a fluidized bed coating machine, the coating process controls the inlet air temperature, the outlet air temperature and the spray rate, and the curing process controls a specific temperature and time.

[0014] Preferably, the filler is selected from at least one of mannitol and lactose; the binder is microcrystalline cellulose; and the lubricant is magnesium stearate.

[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention adopts a ternary polymer matrix compound system. Through the synergistic effect of hydrophilic and hydrophobic components and the structural design of a double-layer core, it achieves efficient stepwise sustained release of different active ingredients. This ensures that the immediate-release ingredients take effect quickly and that the sustained-release ingredients are released stably for a long time. It completely solves the problem that single or binary matrix materials cannot achieve both controlled release and long-term effect.

[0016] 2. This invention effectively inhibits the oxidative degradation of active ingredients through the scientific combination and precise ratio of functional additives. At the same time, the adaptive design of the core and coating layer reduces the interaction between components, significantly improves the stability of the product during storage, and ensures long-term stable release performance.

[0017] 3. The plasticizers, anti-sticking agents, and other additives in this invention are precisely matched with the characteristics of the substrate, and the process parameters are dynamically adjusted according to the characteristics of the raw materials, avoiding problems such as coating layer brittleness, peeling, and bubbling, and significantly improving the integrity of the coating layer. At the same time, the physical properties of the product, such as hardness and brittleness, are optimized, which can meet the stringent requirements of industrial production, transportation, and storage.

[0018] 4. In addition, the raw material selection and process parameter range of the present invention have wide applicability and can be adapted to different types of active ingredients and product specifications, providing flexible and efficient technical support for the development of functional compressed candies and having important industrial application value. Detailed Implementation

[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Example 1: (1) Coating material ratio: The total mass of the solid coating material is calculated as 100 grams: 100% of the polymer substrate (including 45 grams of hydroxypropyl methylcellulose K25M, 35 grams of ethyl cellulose, and 20 grams of polyacrylic acid resin Eudragit RL30D); 9 grams of glycerin as plasticizer (accounting for 12% of the total mass of the polymer substrate); 2 grams of mannitol as pore-forming agent; 0.8 grams of micronized silica gel as anti-blocking agent; 0.8 grams of vitamin E as functional additive; and 200 ml of isopropanol aqueous solution as solvent (isopropanol to water volume ratio 5.5:4.5), ensuring that the solid content of the coating solution is about 25%.

[0021] Preparation process: Coating solution preparation: Stirring at 25℃ for 45 minutes until the polymer matrix is ​​completely dissolved, high-speed shear dispersion at 3000rpm for 25 minutes, and ultrasonic degassing at 300W for 20 minutes; Double-layer core preparation: The inner layer immediate-release core contains 18g (18%) vitamin C, 62g (62%) lactose, 15g (15%) microcrystalline cellulose, and 5g (5%) magnesium stearate; The outer layer sustained-release core contains 12g (12%) astaxanthin, 5g (55%) hydroxypropyl methylcellulose K25M5, 23g (23%) mannitol, and 10g (10%) magnesium stearate; Pressing at 12kN pressure, core diameter 6mm, tablet weight 250mg; Coating process: Inlet air temperature 52℃, outlet air temperature 35℃, spray rate 6ml / min, coating weight gain 6%; Curing at 38℃ for 3.5 hours.

[0022] Example 2: (1) Coating material ratio: The total mass of the solid coating material is calculated as follows: 100% of the polymer substrate (including 85g of hydroxypropyl methylcellulose K100M, 8g of ethyl cellulose, and 7g of polyacrylic acid resin Eudragit RS30D); 4g of diethyl phthalate as plasticizer (accounting for 4.2% of the total mass of the polymer substrate); 18g of polyethylene glycol 8000 as pore-forming agent; 6g of talc as anti-blocking agent; 6g of rosemary extract as functional additive; and 220ml of ethanol aqueous solution as solvent (ethanol to water volume ratio 8.5:1.5), ensuring that the solid content of the coating solution is about 28%.

[0023] (2) Preparation process: Coating solution preparation: Stir at 35℃ for 25 minutes until the polymer substrate is completely dissolved, high-speed shear dispersion at 4000rpm for 12 minutes, ultrasonic degassing at 500W for 8 minutes; Double-layer core preparation: The inner layer immediate-release core contains 22g (22%) vitamin B6, 58g (58%) mannitol, 15g (15%) microcrystalline cellulose, and 5g (5%) magnesium stearate; The outer layer sustained-release core contains 18g (18%) coenzyme Q10, 48g (48%) hydroxypropyl methylcellulose K100M, 24g (24%) lactose, and 10g (10%) magnesium stearate; Pressed at 20kN pressure, core diameter 10mm, tablet weight 350mg; Coating process: Inlet air temperature 63℃, outlet air temperature 45℃, spray rate 9ml / min, coating weight gain 10%; Cured at 48℃ for 1.5 hours.

[0024] Example 3: (1) Coating material ratio: The total mass of the solid coating material is 100 grams: 100% of the polymer matrix (including 60 grams of hydroxypropyl methylcellulose K4M, 25 grams of ethyl cellulose, and 15 grams of polyacrylic acid resin Eudragit RS30D); 22 grams of plasticizer (accounting for 22% of the total mass of the polymer matrix); 10 grams of pore-forming agent lactose; 3 grams of anti-blocking agent talc and 2 grams of micronized silica gel (used in combination); 12 grams of functional additive β-cyclodextrin and 3 grams of tea polyphenols (used in combination); 190 ml of ethanol-isopropanol mixed aqueous solution (ethanol:isopropanol:water = 5:2:3) to ensure that the solid content of the coating solution is about 30%.

[0025] (2) Preparation process: Coating solution preparation: Stir at 30℃ for 35 minutes until the polymer substrate is completely dissolved, high-speed shear dispersion at 3500rpm for 18 minutes, ultrasonic degassing at 400W for 15 minutes; Double-layer core preparation: Inner layer immediate-release core contains 20g (20%) vitamin C, 60g (60%) mannitol, 15g (15%) microcrystalline cellulose, and 5g (5%) magnesium stearate; Outer layer sustained-release core contains 15g (15%) lutein, 50g (50%) hydroxypropyl methylcellulose K4M, 25g (25%) lactose, and 10g (10%) magnesium stearate; Pressed at 16kN pressure, core diameter 8mm, tablet weight 300mg; Coating process: Inlet air temperature 58℃, outlet air temperature 40℃, spray rate 7.5ml / min, coating weight gain 8%; Cured at 42℃ for 2.5 hours.

[0026] Example 4: (1) Coating material ratio: The total mass of the solid coating material is calculated as 100 grams: 100% of the polymer substrate (including 50 grams of hydroxypropyl methylcellulose K15M, 30 grams of ethyl cellulose, and 20 grams of polyacrylic acid resin Eudragit RL30D); 10 grams of triethyl citrate and 5 grams of glycerin (used in combination, accounting for 18.75% of the total mass of the polymer substrate); 15 grams of polyethylene glycol 6000; 4 grams of micronized silica gel as an anti-blocking agent; 1.5 grams of β-cyclodextrin and 2 grams of vitamin E as functional additives (used in combination); and 210 ml of isopropanol aqueous solution (isopropanol to water volume ratio 7:3) to ensure that the solid content of the coating solution is about 26%.

[0027] (2) Preparation process: Coating solution preparation: Stir at 28℃ for 40 minutes until the polymer substrate is completely dissolved, high-speed shear dispersion at 3200rpm for 20 minutes, ultrasonic degassing at 350W for 12 minutes; Double-layer core preparation: Inner layer immediate-release core contains 15g (15%) vitamin B1, 65g (65%) mannitol, 15g (15%) microcrystalline cellulose, and 5g (5%) magnesium stearate; Outer layer sustained-release core contains 16g (16%) coenzyme Q10, 49g (49%) hydroxypropyl methylcellulose K15M, 25g (25%) lactose, and 10g (10%) magnesium stearate; Pressed at 14kN pressure, core diameter 7mm, tablet weight 280mg; Coating process: Inlet air temperature 55℃, outlet air temperature 38℃, spray rate 8ml / min, coating weight gain 9%; Cured at 40℃ for 3 hours.

[0028] Example 5: (1) Coating material ratio: The total mass of the solid coating material is 100 grams: the polymer substrate accounts for 100% (including 55 grams of hydroxypropyl methylcellulose K25M, 20 grams of ethyl cellulose, and 15 grams of polyacrylic acid resin Eudragit RS30D); the plasticizer is 8 grams of diethyl phthalate and 4 grams of glycerin (used in combination, accounting for 13.6% of the total mass of the polymer substrate); the pore-forming agent is 5 grams of lactose and 3 grams of mannitol (used in combination); the anti-adhesion agent is 2 grams of talc and 1 gram of micronized silica gel (used in combination); the functional additives are 4 grams of tea polyphenols and 2 grams of rosemary extract (used in combination); the solvent is 205 ml of ethanol-isopropanol mixed aqueous solution (ethanol:isopropanol:water = 6:1:3), ensuring that the solid content of the coating solution is about 27%.

[0029] (2) Preparation process: Coating solution preparation: Stir at 32℃ for 30 minutes until the polymer substrate is completely dissolved, high-speed shear dispersion at 3800rpm for 15 minutes, ultrasonic degassing at 450W for 18 minutes; Double-layer core preparation: The inner layer instant-release core contains 21g (21%) vitamin C, 59g (59%) mannitol, 15g (15%) microcrystalline cellulose, and 5g (5%) magnesium stearate; The outer layer slow-release core contains 14g (14%) astaxanthin, 51g (51%) hydroxypropyl methylcellulose K25M, 25g (25%) lactose, and 10g (10%) magnesium stearate; Pressed at 18kN pressure, core diameter 9mm, tablet weight 320mg; Coating process: Inlet air temperature 60℃, outlet air temperature 42℃, spray rate 7ml / min, coating weight gain 7%; Cured at 45℃ for 2 hours.

[0030] Comparative Example 1: (1) Coating material The total mass of solid coating material is calculated as 100 grams: only 100 grams of hydroxypropyl methylcellulose K15M is used as the polymer base material; 8 grams of glycerol is used as the plasticizer (accounting for 8% of the total mass of the polymer base material); 5 grams of lactose is used as the pore-forming agent; 3 grams of talc is used as the anti-adhesion agent; 4 grams of β-cyclodextrin is used as the functional additive; and 200 ml of ethanol aqueous solution is used as the solvent (ethanol to water volume ratio 7:3).

[0031] The preparation process is completely consistent with that of Example 1.

[0032] Comparative Example 2: (1) The coating material is exactly the same as in Example 1, but the plasticizer glycerin is removed.

[0033] (2) The preparation process is completely consistent with that in Example 1.

[0034] Comparative Example 3: (1) The coating material is exactly the same as in Example 1, but the amount of mannitol, the pore-forming agent, is increased to 25 grams.

[0035] (2) The preparation process is completely consistent with that in Example 1.

[0036] Comparative Example 4: (1) The coating material is completely the same as that in Example 1.

[0037] (2) The air inlet temperature during the coating process was set to 48°C, and the remaining steps were completely consistent with those in Example 1.

[0038] Comparative Example 5: (1) The coating material is completely the same as that in Example 1.

[0039] (2) Preparation process: In the core preparation stage, a single-layer core is used. Vitamin C and astaxanthin are mixed (mass ratio 1.5:1), and the remaining components are the same as the inner layer immediate-release core in Example 1. The core is pressed into a single-layer core with a diameter of 6 mm and a tablet weight of 250 mg. The coating process is completely the same as in Example 1.

[0040] Performance testing and results analysis: (1) In vitro dissolution test: Test method: Following the dissolution determination method in General Chapter 0931 of the 2020 edition of the Chinese Pharmacopoeia, Part IV, the paddle method was used at a speed of 50 rpm and a temperature of 37℃±0.5℃. The dissolution medium was pH 6.8 phosphate buffer (900 mL). Samples of 5 mL were taken at 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, and 12 hours (with an equal volume of fresh dissolution medium added simultaneously). After filtration through a 0.45 μm filter membrane, the cumulative release rate of immediate-release components (vitamin C, vitamin B6, vitamin B1) and sustained-release components (astaxanthin, coenzyme Q10, lutein) was determined by high-performance liquid chromatography (HPLC).

[0041] Judgment criteria: For immediate-release components, the cumulative release rate after 2 hours is ≥70%; for sustained-release components, the cumulative release rate after 2 hours is ≤30%, after 6 hours is ≤60%, and after 12 hours is ≥80%. Meeting the requirements for stepped sustained-release is considered satisfactory. The test results are shown in Table 1 below: (2) Coating layer integrity test Test method: (1) Appearance observation: Use a 40x optical microscope to observe whether there are cracks or bubbles on the surface of the coating layer. Five different areas are observed for each sample; (2) Friction resistance test: Take 20 samples and put them into a rotary drum friability tester. Rotate at 100 revolutions per minute for 30 minutes. Weigh the total mass of the samples before and after rotation and calculate the coating shedding rate (Shedding rate = (total mass before rotation - total mass after rotation) / total mass before rotation × 100%).

[0042] Judgment criteria: No cracks, no bubbles, and a coating peeling rate of ≤1% are considered to meet the standard.

[0043] The test results are shown in Table 2 below: (3) Stability test Test method: In accordance with the Guidelines for Drug Stability Testing in General Chapter 9001 of Part IV of the 2020 Chinese Pharmacopoeia, the samples were placed in a constant temperature and humidity chamber at 40℃±2℃ and relative humidity of 75%±5% for 3 months. Samples were taken at the end of 1 month, 2 months and 3 months to determine the dissolution rate (dissolution rate = |release rate at the end of 3 months - initial release rate| / initial release rate × 100%) and the retention rate of active ingredient (retention rate of active ingredient = content of active ingredient at the end of 3 months / content of initial active ingredient × 100%).

[0044] Judgment criteria: Dissolution change rate ≤5%, active ingredient retention rate ≥90% is considered to meet the standard.

[0045] The test results are shown in Table 3 below: (4) Physical performance testing Test methods: ① Hardness test: A tablet hardness tester was used, and 5 tablets were tested for each sample. The average value was taken. ② Friability test: According to the 2020 edition of the Chinese Pharmacopoeia, Part IV, General Chapter 0923 Friability Test Method, 6 tablets (total mass about 6.5 grams) were taken and placed in a friability tester. The tablets were rotated 100 times at a speed of 100 rpm. After removing dust, the tablets were weighed and the weight loss was calculated (weight loss = (total mass before rotation - total mass after rotation) / total mass before rotation × 100%).

[0046] Judgment criteria: Hardness ≥ 4.0 kg and weight loss due to brittleness ≤ 1% are considered to meet the standard.

[0047] The test results are shown in Table 4 below: The results from Tables 1, 2, 3, and 4 can be analyzed as follows: (1) Examples 1-5 all meet the requirements of step-release. In Example 3, due to the synergy between the composite functional additives and the composite anti-adhesive, the release rate of the sustained-release component was controlled at 52% after 6 hours and 84% after 12 hours, with a stable release curve. In Comparative Example 1, due to the lack of hydrophobic substrate synergy, the release rate of the sustained-release component reached 58% after 2 hours and 82% after 6 hours, far exceeding the standard, proving the necessity of the ternary substrate compound. In Comparative Example 5, there was no clear immediate / slow-release stratification, and the release of vitamin C and astaxanthin interfered with each other, making it impossible to achieve a step-release effect, verifying the necessity of the double-layer core design.

[0048] (2) The coating peeling rate of Example 3 was only 0.4%, which was better than that of Comparative Example 1 (0.9%) with a single anti-adhesive agent, proving that the composite anti-adhesive agent can improve the coating uniformity; Comparative Example 2 had obvious cracks due to the excessive rigidity of the coating layer, with a peeling rate of 8.5%, verifying the necessity of the plasticizer and the substrate being compatible; Comparative Example 4 had bubbles in the coating layer due to incomplete solvent evaporation, with a peeling rate of 6.2%, proving the importance of matching process parameters with the formulation.

[0049] (3) Stability Example 3 The active ingredient retention rate reached 95%, and the dissolution rate change rate was only 2.5%, which was better than Comparative Example 1 with a single adjuvant, proving the synergistic antioxidant and stabilizing effect of the composite functional adjuvant; Comparative Example 5 was degraded due to the interaction of the active ingredients, and the retention rate was only 84%, verifying the effect of the double-layer core on stability.

[0050] (4) Physical properties Example 2 has a hardness of 5.5 kg, which meets the requirements of a 10 mm large core, and a brittleness of only 0.5%; Comparative Example 2 has a hardness of only 3.0 kg and a brittleness of 2.0% due to the brittleness of the coating layer, which proves the key role of plasticizer in physical properties; Example 5 has a hardness of 5.0 kg and a brittleness of 0.3%, which is the best overall performance and can meet the requirements of industrial transportation and storage.

[0051] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only to the claims and their full scope and equivalents.

Claims

1. A polymeric sustained-release coating material for double-layer sustained-release composite compressed candy and the compressed candy prepared therefrom, characterized in that, The coating material comprises a polymer matrix, plasticizer, pore-forming agent, anti-adhesive agent, functional additives, and solvent; the polymer matrix comprises hydroxypropyl methylcellulose, ethyl cellulose, and polyacrylic acid resin; the compressed candy comprises a double-layer core, the double-layer core including an inner immediate-release core and an outer sustained-release core, the inner immediate-release core comprising an immediate-release active ingredient, filler, binder, and lubricant, and the outer sustained-release core comprising a sustained-release active ingredient, a sustained-release substrate, filler, and lubricant, the sustained-release substrate being compatible with the type of hydroxypropyl methylcellulose in the coating material.

2. The polymeric sustained-release coating material according to claim 1 and the compressed candy prepared therefrom, characterized in that, The hydroxypropyl methylcellulose is selected from at least one of K4M, K15M, K100M, and K25M; the polyacrylic acid resin is selected from at least one of Eudragit RS30D and Eudragit RL30D.

3. The polymeric sustained-release coating material according to claim 1 or 2 and the compressed candy prepared therefrom, characterized in that, The plasticizer is selected from at least one of triethyl citrate, diethyl phthalate, and glycerin.

4. The polymeric sustained-release coating material according to claim 1 or 2 and the compressed candy prepared therefrom, characterized in that, The pore-forming agent is selected from at least one of lactose, polyethylene glycol, and mannitol, and the polyethylene glycol is selected from at least one of type 4000, type 6000, and type 8000.

5. The polymeric sustained-release coating material according to claim 1 or 2 and the compressed candy prepared therefrom, characterized in that, The functional additive is selected from at least one of β-cyclodextrin, tea polyphenols, vitamin E, and rosemary extract; the anti-adhesive is selected from at least one of talc and micronized silica gel; and the solvent is selected from at least one of aqueous ethanol and aqueous isopropanol.

6. A preparation process for a double-layer sustained-release compound compressed candy, characterized in that, Includes the following steps: (1) Preparation of coating solution: The polymer substrate is dissolved in a solvent, then plasticizer, pore-forming agent and anti-adhesion agent are added for dispersion, and finally functional additives are added and degassed to obtain coating solution; the polymer substrate includes hydroxypropyl methylcellulose, ethyl cellulose and polyacrylic acid resin; (2) Preparation of double-layer core: Prepare inner layer fast-release core material and outer layer slow-release core material respectively, and press the two materials in sequence to form a double-layer core; (3) Coating and curing: The coating liquid is coated onto the surface of the double-layer core using a coating equipment, and then cured to obtain a double-layer slow-release composite compressed candy.

7. The preparation process according to claim 6, characterized in that, In step (1), the temperature is controlled within a specific range when dissolving the polymer substrate, the dispersion process adopts high-speed shearing, and the degassing process adopts ultrasonication.

8. The preparation process according to claim 6 or 7, characterized in that, In step (2), a double-layer tablet press is used to press the double-layer core. The pressing process controls a specific pressure. The inner layer immediate-release core material contains immediate-release active ingredients, fillers, binders and lubricants. The outer layer sustained-release core material contains sustained-release active ingredients, sustained-release substrate, fillers and lubricants. The sustained-release substrate is compatible with the hydroxypropyl methylcellulose type in the polymer substrate.

9. The preparation process according to claim 6 or 7, characterized in that, In step (3), the coating equipment is a fluidized bed coating machine. The coating process controls the inlet air temperature, outlet air temperature and spray rate, and the curing process controls a specific temperature and time.

10. The preparation process according to claim 8, characterized in that, The filler is selected from at least one of mannitol and lactose; the binder is microcrystalline cellulose; and the lubricant is magnesium stearate.